1994
DOI: 10.1093/rheumatology/33.10.954
|View full text |Cite
|
Sign up to set email alerts
|

A Double-Blind Placebo Controlled Trial of Efamol Marine on Skin and Joint Symptoms of Psoriatic Arthritis

Abstract: Fish oil may be beneficial in the treatment of psoriasis and in RA. We examined the potential benefit of Efamol Marine, a combination of evening primrose oil and fish oil in the treatment of 38 patients with PsA. Patients with PsA were entered in a double-blind placebo controlled study and received either 12 Efamol Marine capsules or 12 placebo capsules daily for 9 months. All patients received placebo capsules for a further 3 months. At month 3 of the study patients were asked to reduce their intake of NSAIDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 0 publications
1
56
1
Order By: Relevance
“…Mayser et al 16 also found a more than 40-fold increase of LTB5, evidenced from day 3 to day 15, but there was only a slight decrease of chemotactic LTB4 in both intervention and control groups with no significant difference. However, Veale et al 6 did not find any significant improvement by giving n-3 PUFA. LTB4 was found to have significantly decreased in the treatment group (P < 0.03) but not in the control group.…”
Section: Description Of Included Studiesmentioning
confidence: 88%
See 4 more Smart Citations
“…Mayser et al 16 also found a more than 40-fold increase of LTB5, evidenced from day 3 to day 15, but there was only a slight decrease of chemotactic LTB4 in both intervention and control groups with no significant difference. However, Veale et al 6 did not find any significant improvement by giving n-3 PUFA. LTB4 was found to have significantly decreased in the treatment group (P < 0.03) but not in the control group.…”
Section: Description Of Included Studiesmentioning
confidence: 88%
“…Gupta et al 5 reported the mean time period elapsed before the psoriasis worsened to pre-therapy severity was 4.9 AE 0.5 weeks in the intervention group and 4.5 AE 0.6 weeks in the control group (P = 0.4). Veale et al 6 reported no significant changes in articular index or skin itch at the end of the study, yet the subjects in the active treatment group had significantly more skin itch at the beginning (P = 0.03), thus suggesting the implementation of n-3 PUFA may be helpful for skin itch. Although Bjorneboe et al 14 did not find any significant difference between both groups, the total n-3 PUFA in serum phospholipids was significantly increased as compared to pre-treatment values while causing a significant fall in the AA and linoleic acid content of serum phospholipids.…”
Section: Description Of Included Studiesmentioning
confidence: 88%
See 3 more Smart Citations